2016
DOI: 10.1136/thoraxjnl-2015-207559
|View full text |Cite
|
Sign up to set email alerts
|

Prolonged controlled mechanical ventilation in humans triggers myofibrillar contractile dysfunction and myofilament protein loss in the diaphragm

Abstract: Prolonged CMV in humans triggers significant decreases in active and passive diaphragm myofibrillar force generation. This response is mediated, in part, by impaired myosin cross-bridge kinetics and decreased myofibrillar protein levels.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
38
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(42 citation statements)
references
References 47 publications
(46 reference statements)
3
38
0
1
Order By: Relevance
“…Moreover, high levels of oxidative stress and autophagy were linked to apoptotic and proteolytic processes that had consequences in diaphragm dysfunction and developed VIDD in mechanically ventilated patients [2, 21]. However, recent reports suggest that physiological levels of ROS formation and autophagy are essential for cellular signaling and homeostasis [22].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Moreover, high levels of oxidative stress and autophagy were linked to apoptotic and proteolytic processes that had consequences in diaphragm dysfunction and developed VIDD in mechanically ventilated patients [2, 21]. However, recent reports suggest that physiological levels of ROS formation and autophagy are essential for cellular signaling and homeostasis [22].…”
Section: Discussionmentioning
confidence: 99%
“…However, other studies reported a link between higher levels of autophagy and human diaphragm atrophy in mechanically ventilated patients [21]. For examples, Hussain et al reported higher levels of oxidative stress (4-HNE expression) and upregulated autophagy levels (LC3-II/I ratio) and evidence of autophagosome formation in chronically ventilated patients (average MV time 59 ± 16.5 h) in comparison with a control group (2–4 h of MV) [2, 21]. Also, animal studies have shown that diaphragm function preservation was accompanied by lower levels of oxidative stress and autophagy [20].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…With respect to muscle contractility, one study found no changes in the force generated by permeabilized diaphragm fibers from brain-dead organ donor patients after an average mechanical ventilation period of 26 h [20]. However, another recent study with a longer (49 h) average period of mechanical ventilation reported decreased active as well as passive force production by isolated diaphragm myofibrils [21].…”
Section: Does Mechanical Ventilation Impair Diaphragmatic Function?mentioning
confidence: 96%
“…Hussain and colleagues provide us with this important missing proof-of-concept information on the effects of VIDD on diaphragmatic contractility in humans and explore underlying mechanisms 15. These investigators obtained diaphragm biopsies from 13 subjects undergoing cardiac surgery (control group) and 12 brain-dead organ donors (CMV group).…”
mentioning
confidence: 99%